Market and society in Korea : interest, institution, and the textile industry - McNamara, Dennis L. (Routledge, 2002)
Stretching from high technology to labour-intensive production, the textile industry offers a new profile of democratization and market liberalization, and recently of globalization and adjustment in the wake of the Asian financial crisis."--Cover
Keywords: Textile industry -- Korea (South); Korea (South) -- Economic conditions -- 1960-1988.; Textiles et tissus -- Industrie et commerce -- Corée du Sud.; Corée du Sud -- Conditions économiques -- 1960-1988.; BUSINESS & ECONOMICS -- Industries -- Fashion & Textile Industry.; Economic history; Textile industry; Korea (South); 1960-1988